Double-Locking Mechanism of Self-Compatibility in Arabidopsis thaliana: The Synergistic Effect of Transcriptional Depression and Disruption of Coding Region in the Male Specificity Gene - Suwabe, Keita; Nagasaka, Kaori; Windari, Endang Ayu; Hoshiai, Chihiro; Ota, Takuma; Takada, Maho; Kitazumi, Ai; Masuko-Suzuki, Hiromi; Kagaya, Yasuaki; Yano, Kentaro; Tsuchimatsu, Takashi; Shimizu, Kentaro K.; et al. (Frontiers in Plant Science, 2020)
Self-compatibility in Arabidopsis thaliana represents the relatively recent disruption of ancestral obligate cross pollination, recognized as one of the prevalent evolutionary pathways in flowering plants, as noted by Darwin. Our previous study found that inversion of the male specificity gene (SP11/SCR) disrupted self-incompatibility, which was restored by overexpressing the SCR with the reversed inversion. However, SCR in A. thaliana has other mutations aside from the pivotal inversion, in both promoter and coding regions, with probable effects on transcriptional regulation. To examine the functional consequences of these mutations, we conducted reciprocal introductions of native promoters and downstream sequences from orthologous loci of self-compatible A. thaliana and self-incompatible A. halleri. Use of this inter-species pair enabled us to expand the scope of the analysis to transcriptional regulation and deletion in the intron, in addition to inversion in the native genomic background. Initial analysis revealed that A. thaliana has a significantly lower basal expression level of SCR transcripts in the critical reproductive stage compared to that of A. halleri, suggesting that the promoter was attenuated in inducing transcription in A. thaliana. However, in reciprocal transgenic experiments, this A. thaliana promoter was able to restore partial function if coupled with the functional A. halleri coding sequence, despite extensive alterations due to the self-compatible mode of reproduction in A. thaliana. This represents a synergistic effect of the promoter and the inversion resulting in fixation of self-compatibility, primarily enforced by disruption of SCR. Our findings elucidate the functional and evolutionary context of the historical transition in A. thaliana thus contributing to the understanding of the molecular events leading to development of self-compatibility.